Zambia - Commercial Value Chains in Zambian Agriculture : Do Smallholders Benefit? - World Bank (World Bank, 2012)
Agriculture and agroprocessing are important in Zambia's economy, representing more than 40 percent of gross domestic product (GDP) and contributing about 12 percent of national export earnings. Agriculture employs some 67 percent of the labor force and supplies raw materials to agricultural industries, which account for some 84 percent of manufacturing value-added in the country. Smallholder agriculture dominates the rural economy. It provides livelihoods for the overwhelming majority of rural households. The commercialization of smallholder agriculture is an important element of Zambia's strategy to increase economic growth in an equitable manner and diversify smallholder agriculture. This study therefore asks: 'do Zambian smallholders benefit from greater participation in value chains?' It provides an evidence-based analysis of the benefits and constraints associated with smallholders' integration into specific commercial value chains. The study also investigates whether the benefits of participating in these value chains can be increased for smallholders and provides corresponding policy and investment recommendations.